Impacts of the invasive alien plant species Caesalpinia decapetala on plant community diversity and composition in Alta Wondo District, Southern Zone, Sidama Region, Ethiopia - Amare Assefa; Gebiyaw Tilaye (Sustinere: Journal of Environment and Sustainability, 2026)
Caesalpinia decapetala has been ranked as a high-impact invasive alien plant species in Ethiopia. Therefore, the objective of this study was to investigate the impact of Caesalpinia decapetala on species diversity and the composition of invaded plant communities in the study area. Accordingly, quadrats were systematically laid along the transect line in both invaded and non-invaded study areas. A total of 78 (10 m x 10 m) quadrats were sampled, comprising 39 quadrats each from invaded and non-invaded areas, to examine the effect of Caesalpinia decapetala on species diversity and composition. The results indicated that species richness declined from 59 to 38 species (−35.59%), Shannon diversity index H′ decreased from 3.20 to 1.10 (−65.63%), Simpson’s 1−D decreased from 0.82 to 0.29 (−64.63%), and evenness declined from 0.76 to 0.37 (−51.32%) in invaded areas compared to non-invaded areas. A Generalized Linear Model (GLM) fitted with a Poisson distribution revealed a significant negative relationship between Caesalpinia decapetala cover and species richness (β = −0.03, p < 0.001), suggesting that increasing invasion levels are associated with exponential declines in plant biodiversity. Hence, Caesalpinia decapetala is one of the factors affecting the biodiversity in the study areas. Immediate integrated management interventions are therefore warranted to curb biodiversity loss.